Open and clean: the healthy nose - Ciprandi, Giorgio; Gelardi, Matteo (Acta Biomedica Atenei Parmensis, 2019)
The nose exerts many functions, mainly for the respiration and the olfaction and represents the first doorway for the oxygen, but also for pathogens. The present Supplement reports some clinical experiences concerning the use of a new internal nasal dilator in different settings, including nasal obstructive disorders, obstructive sleep apnea syndrome, continuous positive active pressure (CPAP), and sport activity. The outcomes support the concept that a healthy nose should be maintained ever patent and free from secretions, as impaired nasal function can significantly affect quality of life. Therefore, an “open and clean nose” contributes in a relevant way to the subjective wellness.